Switching categories in syntax - Paula Armelin; Dalila Maria de Souza; Lydsson Gonçalves (Isogloss)
This paper investigates the relationship between infinitival nominalizations and analytical passives in Brazilian Portuguese. Taking Distributed Morphology as a theoretical framework (Halle & Marantz 1993; Marantz 1997), we propose a parallel structure for these formations based on the important similarities they present. Specifically, we propose that the derivation of both these structures includes a projection of a mixed nature, a Switch head (Panagiotidis 2015), which carries features of two different categories and thus can interrupt an extended projection and begin a new one. In this case, the Switch makes the originally verbal structure to become nominal. We argue that the distinction between nominal infinitives and passives is that in the former, the Switch carries an [N] feature, while in the latter, it brings an [A] feature to the structure. Infinitival nominalizations, thus, are formally nouns, as evidenced by their compatibility with determiners and different argument positions prototypically associated with nouns. In passives, this operation results in participles, which behave like adjectives: they do not admit a determiner, they have unvalued φ-features and they need a copular verb to be projected into a verbal structure.